Effect of Rapid Solidification Processing on the Microstructure and Corrosion of 316L Austenitic Stainless Steel - Apolinario,Raíra Chefer (2022)
Austenitic stainless steels processed by rolling are widespread in technological applications, since they have excellent mechanical and corrosion properties. This study investigated the effect of the cooling rate, microstructure and properties of 316L austenitic stainless steel under cold rolled conditions and by rapid solidification. The microstructure of the cold rolling processing steel was composed of austenite and a low percentage of delta ferrite. For the rapid solidification condition, the microstructure evolved from columnar and acicular dendrites to equiaxed dendrites with decreasing cooling rates, without the presence of delta ferrite due to the high cooling rate. Furthermore, thermal analyses in both routes revealed that oxidation kinetics was slower after rapid solidification in synthetic air. The microhardness in the cold rolling condition was lower than in the rapid solidification condition since the microstructure under the solidification condition is more refined. The sample in the rapid solidification condition region RS1 presented the highest corrosion resistance considering the pit potential. The passivation current density in the cold rolled condition was 5.72x10-5A/cm2, while under the rapid solidification condition, regions RS1 and RS2 were 2.24x10-5 A/cm2 and 3.72x10-6 A/cm2, respectively, and region RS3, did not present a passivation region in a broad range of potentials.